Bibliometric Analysis of Religious Education Systems in Schools: Trends, Themes, and Future Directions - Latifatul Inayati, Nurul; Rohmani, Annas Fajar (Multicultural Islamic Education Review, 2025)
This study conducts a bibliometric analysis of research on "Religious Education Systems in Schools" to identify trends, themes, and future directions. Data was sourced from the Scopus database covering 1915–2024, with 723 relevant documents analyzed using tools such as R, RStudio, VOSviewer, and Microsoft Excel. A systematic three-stage process was employed to assess publication trends, thematic clusters, and relationships among research elements. The results indicate a steady growth in publications, particularly after 2000, with a peak in 2023. Key themes include integrating religious values into curricula, the role of religious education in shaping national identity, and emerging topics on gender and diversity. Dominant keywords such as "education," "curriculum," and "multiculturalism" emphasize the focus on inclusivity and innovation. Countries like the USA, UK, and Israel lead in research output, while Indonesia emerges as a significant contributor from the Global South. The study highlights opportunities for future research, including integrating technology in religious education, fostering interreligious dialogue, and addressing social equity through inclusive frameworks. This bibliometric analysis provides a roadmap for educators, researchers, and policymakers to enhance the relevance, inclusivity, and global impact of religious education in schools amidst evolving societal challenges.